The idea of the Polish Association of Transport Engineers & Technicians in professional life - Paweł Gradowski (Przegląd Komunikacyjny)
Abstract: One of the basic goals set for the Polish Association of Transport Engineers and Technicians is to increase the professional qualifications of the staff. Such development is possible through the exchange of knowledge at various thematic meetings also organized by, inter alia SITK RP. Using the example of the Works Group, the author presents the possibilities of promoting the idea of the Association in his professional life.